Virologic outcomes in early antiretroviral treatment: HPTN 052 - Susan H. Eshleman (2018)
© 2017 Informa UK Limited, trading as Taylor & Francis Group. Introduction: The HIV Prevention Trials Network (HPTN) 052 trial demonstrated that early antiretroviral therapy (ART) prevented 93% of HIV transmission events in serodiscordant couples. Some linked infections were observed shortly after ART initiation or after virologic failure. Objective: To evaluate factors associated with time to viral suppression and virologic failure in participants who initiated ART in HPTN 052. Methods: 1566 participants who had a viral load (VL)  >  400 copies/mL at enrollment were included in the analyses. This included 832 in the early ART arm (CD4 350–550 cells/mm 3 at ART initiation) and 734 in the delayed ART arm (204 with a CD4  <  250 cells/mm 3 at ART initiation; 530 with any CD4 at ART initiation). Viral suppression was defined as two consecutive VLs ≤ 400 copies/mL after ART initiation; virologic failure was defined as two consecutive VLs  >  1000 copies/mL  >  24 weeks after ART initiation. Results: Overall, 93% of participants achieved viral suppression by 12 months. The annual incidence of virologic failure was 3.6%. Virologic outcomes were similar in the two study arms. Longer time to viral suppression was associated with younger age, higher VL at ART initiation, and region (Africa vs. Asia). Virologic failure was strongly associated with younger age, lower educational level, and lack of suppression by three months; lower VL and higher CD4 at ART initiation were also associated with virologic failure. Conclusions: Several clinical and demographic factors were identified that were associated with longer time to viral suppression and virologic failure. Recognition of these factors may help optimize ART for HIV treatment and prevention.